Upaya Penanganan Gangguan Nyeri Akut Pada An. C Dengan Faringitis - Setiawan, Ahmad Tri, Irdawati, S.Kep.,Ns.,M.Si.,Med, Siti Arifah, S.Kp.,M.Kes (2017)
Background: An estimated 15 million cases of pharyngitis diagnosed annually in the United States by 15-30% in school-age children and 10% suffered by adults and 20-30% of cases are caused by SBHGA. Pharyngitis is not influenced by gender. Period SBHGA infections occur in the winter and the beginning of a spring in temperate climates, in tropical areas such as Indonesia highest incidence occurs during the rainy season. Data visits patients in the clinic ENT-KL Hospital Dr. Mohammad Hoesin Palembang in 2011 showed as many as 726 people visit acute pharyngitis of total 7256 visits (± 10%). Objective: To investigate the nursing care of patients with acute pharyngitis include assessment, intervention, implementation and evaluation of nursing. Methods: scientific papers collated using descriptive method with case study approach by collecting data, analyzing the data and draw conclusions. Results: After 3x24-hour nursing care for disorders showed a sense of comfort (acute pain) patient pain scale was reduced from 5 to 2, back effective airway clearance, increased knowledge of patients and families about the disease faringitis.Kesimpulan: Cooperation among the health care team with patient or family is indispensable for the success of nursing care in An. C, therapeutic communication can encourage a more cooperative patient